Posttranslational modifications of proteins : (Humana Press, 2002)
Posttranslational Modifications of Proteins: Tools for Functional Proteomics is a compilation of detailed protocols needed to detect and analyze the most important co- and posttranslational modifications of proteins. Though, for reasons of simplicity not explicitly mentioned in the title, both kinds of modifications are covered, whether they occur during, or after, biosynthesis of the protein. My intention was to cover the most significant protein modifications, focusing on the fields of protein function, proteome research, and the characterization of pharmaceutical proteins.